Photonic-chip assisted correlative light and electron microscopy - Tinguely, Jean-Claude (Commun Biol, 2020)
Correlative light and electron microscopy (CLEM) unifies the versatility of light microscopy (LM) with the high resolution of electron microscopy (EM), allowing one to zoom into the complex organization of cells. Here, we introduce photonic chip assisted CLEM, enabling multi-modal total internal reflection fluorescence (TIRF) microscopy over large field of view and high precision localization of the target area of interest within EM. The photonic chips are used as a substrate to hold, to illuminate and to provide landmarking of the sample through specially designed grid-like numbering systems. Using this approach, we demonstrate its applicability for tracking the area of interest, imaging the three-dimensional (3D) structural organization of nano-sized morphological features on liver sinusoidal endothelial cells such as fenestrations (trans-cytoplasmic nanopores), and correlating specific endo-lysosomal compartments with its cargo protein upon endocytosis.